EVALUASI KETERSEDIAAN NUTRIEN DALAM CORNDRIED DISTILLER GRAIN WITH SOLUBLES (CORN-DDGS) SEBAGAI PAKAN PUYUH JANTAN - , Hestu Widyatmoko, Prof. Dr. Ir. Zuprizal DEA. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The objective of this study was to evaluate Corn Distillers Dried Grains With Solubles (Corn-DDGS) as ingridient of coturnix feed. Observed variables were the chemical content, protein molecular weight, amino acid composition, protein digestibility in vitro, metabolism energy (ME), and growth performance. Chemical content include: crude protein (CP), ekstract eter (EE), crude fiber (CF), ash, calcium (Ca) and phosphorus (P). Crude protein, EE, CF, and ash were determined by proximate method analysis, mineral Ca with EDTA method by titration and P was determined by spectrophotometry, determination of molecular weight of proteins by electrophoresis with SDS-PAGE method, determination of amino acids using high performance liquid chromatography (HPLC), protein digestibility in vitro with Whalphole method, male coturnix metabolism energy using the wet force feeding, while the growth performance test using feeding trial method using four different level of DDGS (0, 10, 20, and 30%). Proximate analysis results that DDGS, containing CP, EE, CF, ash, Ca, and P 1.14% were 25.63